1990
DOI: 10.1093/nar/18.19.5853
|View full text |Cite
|
Sign up to set email alerts
|

A distal dimerization domain is essential for DNA-binding by the atypical HNF1 homeodomain

Abstract: Hepatic Nuclear Factor 1 (HNF1, also referred to as LFB1, HP1 or APF) is a liver-specific transcription factor required for the expression of many hepatocyte specific genes. We report here the purification of this rat liver nuclear protein and the cloning of its cDNA using a PCR-derived approach. Seven independent clones reveal 3 alternative polyadenylation sites and a unique open reading frame. Both a motif homologous to the homeodomain and a distal dimerization domain are required for specific DNA binding. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 49 publications
3
104
0
Order By: Relevance
“…HNF-1α staining was also detected in the stomach and intestine, but was not detected in the brain and heart. This restricted pattern of HNF-1α staining was compatible with the reported tissue distribution of HNF-1α mRNA [3,4,5,30,31] and β-galactosidase expression of HNF-1α (+/-) mice [6]. Furthermore, HNF-1α immunoreactivity was absent from the nuclei of hepatocytes in HNF-1α (-/-) mice (Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…HNF-1α staining was also detected in the stomach and intestine, but was not detected in the brain and heart. This restricted pattern of HNF-1α staining was compatible with the reported tissue distribution of HNF-1α mRNA [3,4,5,30,31] and β-galactosidase expression of HNF-1α (+/-) mice [6]. Furthermore, HNF-1α immunoreactivity was absent from the nuclei of hepatocytes in HNF-1α (-/-) mice (Fig.…”
Section: Resultssupporting
confidence: 87%
“…Although HNF-1α was initially identified as a hepatocyte-specific transcription factor, it is known also to be expressed in the pancreas [3,4,5,6]. We have found that heterozygous mutations of the HNF-1α gene cause a form of maturity-onset diabetes of the young (MODY3) [7] and clinical studies have shown that MODY3 is characterized by impaired insulin secretion [8,9], suggesting an important role of HNF-1α in pancreatic beta cells.…”
mentioning
confidence: 99%
“…Previous studies have shown that HNF-I~, as originally postulated ), binds to its recognition sequence as a dimer (Frain et al 1989;Chouard et al 1990;Nicosia et al 1990) and that this dimerization, which occurs in the absence of DNA, is dependent on the 30 amino acids at the extreme amino terminus of HNF-I~ (Chouard et al 1990;Nicosia et al 1990). The observation that the dimerization domain of HNF-loL is conserved in HNF-113, and that the dimerization domain is required for HNF-113 to bind DNA (Fig.…”
Section: Hnf-i[3 Is Able To Form Heterodimers With Hnf-la In Vitromentioning
confidence: 85%
“…HNF-1 is unique among mammalian homeo domaincontaining proteins in that it contains a 21-amino-acid "loop" between helixes 2 and 3 of the homeo domain (Baumhueter et al 1990;Finney 1990) and it forms homodimers in solution (Chouard et al 1990;Nicosia et al 1990). The ability of HNF-1 to dimerize in solution, combined with the observation that a subset of the HNF-1-dependent genes are expressed in tissues and at various times in development, which appear inconsistent with the known expression pattern of HNF-1 (Baumhueter et al 1990), have raised the possibility that the function of the HNF-l-binding site could be diversified somehow developmentally either by the binding of other proteins or by developmental modifications of HNF-1.…”
mentioning
confidence: 99%
“…Hepatocyte nuclear factor 1a is a transcription factor that is implicated in hepatocyte differentiation and is required for the liver-specific expression of several genes, including b-fibrinogen, albumin and a1-antitrypsin (Frain et al, 1989;Baumhueter et al, 1990;Cereghini et al, 1990;Chouard et al, 1990). Heterozygous germline mutations of TCF1/HNF1a have been linked to the occurrence of MODY3 (maturity onset diabetes of the young, OMIM no.…”
Section: Genetic Alterations and Hepatitis B Virus Infectionmentioning
confidence: 99%